Abdominal obesity and osteoarthritis risk: evaluating the association of lipid accumulation product, body roundness index, and waist triglyceride index with osteoarthritis in U.S. adults - Li, Yuanchao; Lai, Congmin; Pan, Zhiming; He, Yanan; Liu, Chunlong (Frontiers in Nutrition, 2025)
ObjectiveThis study explored the associations between lipid accumulation product (LAP), body roundness index (BRI), and waist triglyceride index (WTI) and osteoarthritis (OA) in U.S. adults, using data from National Health and Nutrition Examination Survey (NHANES) 2015–2018.MethodsThis cross-sectional analysis included 3,611 participants aged ≥20 years. Using survey-weighted procedures, multivariable logistic regression assessed associations between anthropometric indices and OA. Smooth curve fitting evaluated non-linear relationships and threshold effects. Segmented linear regression was applied to identify potential inflection points. Subgroup analyses explored demographic and health-related variations, while receiver operating characteristic (ROC) curves assessed the discriminative capacity of these anthropometric indices.ResultsAmong participants, 517 (14.31%) had OA. All indices showed positive associations with OA after adjustment: LAP (OR: 1.19, CI: 1.13–1.25), BRI (OR: 1.02, CI: 1.01–1.02), and WTI (OR: 3.72, CI: 2.25–6.16). LAP significantly increased OA risk below 131.16 (OR: 1.02, p < 0.001) but not above. BRI demonstrated a linear relationship with OA without significant threshold effects (p = 0.190). WTI demonstrated dramatically increased risk above 8.72 (OR: 74.40) vs. below (OR: 4.70). Significant interactions were observed for gender with BRI (p = 0.0145) and hyperlipidemia with LAP (p = 0.0024). Stronger associations appeared in participants with lower education, non-smokers (for BRI), and those with hypertension (for WTI). BRI showed higher diagnostic accuracy [area under the curve (AUC): 0.6588].ConclusionCentral obesity-related indices demonstrate significant associations with OA prevalence in U.S. adults, with distinct threshold effects for LAP and WTI. These indices, particularly BRI, may serve as valuable screening tools for OA risk assessment in clinical practice.